Placing problematic media use in context: a research synthesis, person-centric framework, and chart review among a clinical sample of US youth - Carter, Michael C.; Powell, Nicole; Bediou, Benoit; Tsappis, Michael; Bickham, David; Rich, Michael (Frontiers in Psychiatry, 2025)
Understanding the dynamics underlying problematic media use (PMU) is crucial in today’s digital society. The maintaining factors driving problematic use span both bio-psychological and social factors, necessitating the development of an integrative, meta-theoretical account of PMU to encompass core pathways across established frameworks. The present study used a mixed-methods approach to analyze patient charts (N = 205) from a US clinic specializing in addressing PMU. In doing so, we developed the Person–Context–Process–Outcome–Time (PC-POT) model. PC-POT approaches PMU as a cycle of media-dependent dysfunction. Results suggested that this cycle compounds in severity over time and is maintained by a set of (intrapersonal and interpersonal) situational transitions that can affect patient functioning across five key domains. By providing a heuristic structure that more holistically encompasses core determinants and outcomes of PMU, PC-POT helps to provide a more unified basis to advance understanding of PMU in a person- and process-centric way.